Singularity-free adaptive fault-tolerant trajectory tracking controller for VTOL UAVs. Issue 10 (27th July 2017) - Zou, Yao
ABSTRACT: This paper exploits a singularity-free adaptive fault-tolerant controller for vertical take-off and landing (VTOL) unmanned airborne vehicles (UAVs) to fulfill trajectory tracking manoeuvres, which is robust against parametric uncertainties, actuator faults and unexpected disturbances. Under the hierarchical control framework, the position and attitude loop controls are developed in sequence based on adaptive sliding mode control schemes. Initially, using the saturation property of the hyperbolic tangent function, a position loop controller is synthesised, and a criterion for choosing control parameters is established to guarantee the singularity-free command attitude extraction. Then, in the attitude loop, to avoid singularity which occurs when the pitch reaches± π 2, a novel sliding mode surface is introduced, and an attitude control project with the associated initial condition constraint is put forward. In addition, adaptive algorithms are developed to estimate and compensate the uncertainties arising from unknown inertial parameters, thrust and torque faults and undesired disturbances. It is demonstrated in terms of Lyapunov theorem that, with the proposed controller, the closed-loop position and attitude error subsystems of the VTOL UAV are asymptotically stable, respectively. Eventually, simulations validate the tracking performance of the controller.